2013
DOI: 10.7314/apjcp.2013.14.6.3549
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of Intestinal Metaplasia in Gastric Biopsy of Patients with Dyspepsia in Guilan Province, North Iran

Abstract: Background: It is generally accepted that gastric carcinomas are preceded by a sequential multistage process that includes chronic gastritis, gastric atrophy, usually with intestinal metaplasia (IM), and dysplasia. This series of changes in gastric carcinogenesis is often initiated by Helicobacter pylori (H pylori) infection. The aim of the present study was determination of gastric histopathologic changes in IM patients after at least one year in Guilan province, Iran. Materials and Methods: This case-series … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 41 publications
2
12
0
1
Order By: Relevance
“…Incomplete IM shows transformed cells that contain goblet cells and rudimentary villi associated with the colon. 2 A report by Ono et al 3 described flat, ulcerated, peristomal IM as well as peristomal polypoid IM, as seen in our case. Both polypoid and flat IM lacked epidermis and exposed red macerated mucosa-like tissue.…”
Section: Discussionsupporting
confidence: 72%
“…Incomplete IM shows transformed cells that contain goblet cells and rudimentary villi associated with the colon. 2 A report by Ono et al 3 described flat, ulcerated, peristomal IM as well as peristomal polypoid IM, as seen in our case. Both polypoid and flat IM lacked epidermis and exposed red macerated mucosa-like tissue.…”
Section: Discussionsupporting
confidence: 72%
“…Thirty-two articles were included in the systematic review (Supplementary Tables S1 and S2). Fifteen studies were conducted in Asia [26][27][28][29][30][31][32][33][34][35][36][37][38][39][40] (five from Japan, four from China, three from Korea, two from Iran and one from Taiwan), eight in Europe [41][42][43][44][45][46][47][48] (a multicentre study and one each from England, Finland, Italy, Netherlands, Poland, Portugal and Spain), four in North America [49][50][51][52] (participants were Asian/Hawaiian in two of them), three in South America [53][54][55] [38,42] included participants referred due to gastrointestinal complaints as well as volunteers, and one study [34] recruited first-degree relatives of gastric cancer patients.…”
Section: Systematic Reviewmentioning
confidence: 99%
“…A total of 13 articles [26,27,31,[39][40][41][43][44][45][46][47]49,57] included in the systematic review were not included in the meta-analysis as they did not provide enough information to compute quantitative estimates regarding the exposure to tobacco, compared exposure or outcome categories not directly comparable with those presented in most of the other reports, or evaluated only H. pylori-infected subjects ( Supplementary Table S2).…”
Section: Studies Not Considered For Meta-analysismentioning
confidence: 99%
See 1 more Smart Citation
“…This could be related to individual or environmental factors. Some studies also showed that H. pylori and gastric atrophy might be associated with gastric cancer in Iran (Malekzadeh et al, 2004(Malekzadeh et al, , 2009Mansour-Ghanaei et al, 2013). The progression of precancerous lesions to gastric adenocarcinoma takes a long period of time; therefore, early detection of these lesions will enable the management of these cases more efficiently.…”
Section: Introductionmentioning
confidence: 95%